MANAGEMENT OF INNOVATIVE DEVELOPMENT OF THE TECHNICAL AND TECHNOLOGICAL POTENTIAL OF AGRICULTURAL ENTERPRISES - KRYUKOVA, Irina; KRAVCHYK, Yurii; VOLOSHCHUK, Maksym; KHAKHALIEV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Achieving the goals of agribusiness and increasing the competitiveness of agricultural formations is impossible without the proper provision of technical and technological means. In recent years, significant challenges to technical and technological support have arisen in Ukraine’s agriculture, the solution of which is expedient only under modern conditions, based on innovative development. The article considers problematic aspects of managing the technical support of agricultural producers (a significant gap in the level of technical support of agriculture in Ukraine and the world, the high cost of innovative technical and technological solutions and the lack of financial resources of agricultural producers, the decline of the infrastructure of rural areas, the low level of state financial support for the technological modernization of agriculture, conservatism in the management of personnel of agricultural formations). Specific features are identified form new requirements for the modern management system of innovative development of the technical and technological potential of agricultural enterprises. Among these are: the strategic nature and orientation towards the goals of sustainable development in agribusiness and rural areas; organizational and managerial requirements; technological requirements; information-analytical and infrastructure requirements. The guidelines for developing a management system to enhance the technical and technological potential of agribusiness, based on innovation and the greening of agriculture, are substantiated. The main ones, according to the authors, should be: strategic planning of innovations, dissemination of digital solutions, resource and energy efficiency, risk management and financing of innovations, education and training of personnel, environmental aspects, and sustainable development. Among the priority areas for improving management solutions to increase and implement the technical and technological potential of agricultural enterprises, the following are recommended: financial leasing, digital data platforms, unmanned agricultural machinery, Internet of Things sensors, robotics and automation, and the organization of complex smart farms.